2014
DOI: 10.1227/neu.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Management of Atypical Cranial Meningiomas, Part 1

Abstract: Brain invasion and high mitotic rates may predict recurrence. After GTR of AMs, EBRT appears not to affect progression-free survival and overall survival, suggesting that observation rather than EBRT may be indicated after GTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Radiation therapy to treat meningiomas in general is used when there is residual tumor after surgical resection or to treat recurrence of the tumor [11,26,27]. In our study we found that patients who received radiation had earlier tumor related death as compared to patients who did not receive radiation.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Radiation therapy to treat meningiomas in general is used when there is residual tumor after surgical resection or to treat recurrence of the tumor [11,26,27]. In our study we found that patients who received radiation had earlier tumor related death as compared to patients who did not receive radiation.…”
Section: Discussionmentioning
confidence: 49%
“…Further, there may be large inter-institutional discrepancies in the use of radiation therapy for AAM patients. Early adjuvant radiation for AAM has been analyzed in a multicenter study and was not found to be beneficial to atypical meningioma patients [11,28] This lack of effect on survival or PFS was independent of extent of resection, however, there was selection bias present in this study. Other studies have shown benefit of radiation therapy in PFS but not in OS [19,29,30].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Several previous studies have attempted to address the controversy about whether PORT can improve the outcome in atypical meningioma patients undergoing GTR. Some studies did not show significant survival benefit from PORT in these patients (8, 1014). However, the missing significance has been suspected as a result of small sample size, and some studies also found a contradictory result that PORT could improve the outcome (6, 7, 9, 15).…”
Section: Discussionmentioning
confidence: 90%
“…Radiosurgery may offer greater patient convenience, less adverse effects, and similar local control to traditional XRT techniques [ 9 ]. While it has been used for some time in the definitive or salvage settings for inoperable patients, reports of adjuvant SRS for resected lesions are rare [ 9 - 12 ].…”
Section: Introductionmentioning
confidence: 99%